Refractory angina pectoris: a 20-year (2003–2022) bibliometric analysis - Chen, Yunru; Ge, Yaru; Chao, Tiantian; Huan, Na; Liu, Wenjie; Chu, Guojie; Wang, Chenglong (Frontiers in Cardiovascular Medicine, 2023)
Background The increasing number of patients with refractory angina pectoris, combined with the aging population and improved survival rates among coronary heart disease patients, presents a significant challenge in contemporary cardiovascular medicine. The treatment of refractory angina has been an ongoing area of exploration, yet a comprehensive analysis of the existing literature on this topic is currently lacking. Therefore, this study aims to provide the first bibliometric analysis of publications related to refractory angina. Methods A systematic search was conducted in the Web of Science database to identify articles related to refractory angina published between 2003 and 2022. The inclusion criteria were limited to articles and reviews written in English. CiteSpace software was utilized to conduct a collaborative network analysis of countries/regions, institutions and authors, co-occurrence analysis of keywords, and co-citation analysis of authors and references. Results A total of 1,386 publications were identified, with an annual publication volume exhibiting fluctuation over time. American and European countries and institutions demonstrated a leading position in terms of research output. Henry TD emerged as the most prolific researcher in the field, while Mannheimer C received the highest number of citations. The primary research hotspot within this field focused on the treatment of refractory angina, with recent emphasis on emerging treatments such as stem cell therapy and the coronary sinus reducer. A significant number of clinical trials have been conducted, with a continuous focus on patient benefits, quality of life, and survival prognosis. Conclusion Significant progress has been made in the field of refractory angina pectoris in recent years. Novel treatment methods, including spinal cord stimulation, enhanced external counterpulsation, stem cell therapy, and the coronary sinus reducer, hold promising therapeutic prospects. However, further high-quality evidence-based research is essential to support these emerging interventions. Additionally, the development of comprehensive evidence-based guidelines for refractory angina treatment is crucial. Such guidelines would provide clinicians with a framework to navigate the complexities of treatment choices and optimize patient care in this challenging condition.